Quantitative analysis of professional basketball: A qualitative discussion - Zhou, Y.; Li, T. (Journal of Sports Analytics, 2023)
Quantitative analysis of professional basketball become an attractive field for experienced data analysts, and the recent availability of high-resolution datasets pushes data-driven basketball analytics to a higher degree. We present a qualitative discussion on quantitative professional basketball. We propose and discuss the dimensions, the levels of granularity, and the types of tasks in quantitative basketball. We review key literature in the past two decades and map them into the proposed qualitative framework, with an evolutionary perspective and an emphasis on recent advances. A list of questions around professional basketball that could be approached with quantitative tools is displayed, pointing to directions for future research. We touch on the new landscapes of virtual basketball at enriching the space for quantitative analysis. This report serves as a qualitative primer for quantitative analysis of professional basketball, exhibiting the growing prospect of the promising research area.